Recurrent upper respiratory tract infections in early childhood: a newly defined clinical condition - Antonio Corsello; Gregorio Paolo Milani; Marina Picca; Roberto Buzzetti; Romeo Carrozzo; Mirko Gambino; Giovanni Chiaffoni; Paola Marchisio; Chiara Mameli (BMC, 2024)
Abstract Background Recurrent Upper Respiratory Tract Infections (R-URTIs) pose a significant challenge in pediatric healthcare, affecting both children and their families. This study aimed to investigate the prevalence, risk factors, and clinical implications of R-URTI in children aged 0-5 years. Methods This observational study involved a sample of 483 children aged 0-5 years, focusing on establishing a practical and dynamic definition of R-URTI. Family pediatricians prospectively collected socio-demographic information, medical history, and recorded the occurrence of URTI episodes. Children were followed from recruitment until March 2021, predating the COVID-19 outbreak. Results A substantial prevalence of R-URTIs was found, estimating it at 5-10% among this age group. To define R-URTI, a practical and dynamic criterion was proposed: children experiencing a minimum of four URTI episodes, each lasting four days or more, within a six-month period, with intervals of well-being in between. Conclusions The study highlighted that specific risk factors for R-URTI were elusive, suggesting that this condition may affect children regardless of their family or clinical history. Moreover, the study's stratification by age group and times of observation facilitated patient-specific clinical decision-making. The proposed definition may represent a valuable tool for clinicians in diagnosing and addressing R-URTI cases.